Assessing the phenylketonuria (PKU) neonatal screening program and the incidence rates of PKU in Kerman County, Iran: a health system research - Esmat Rezabeigi Davarani; Fatemeh Mohseni Takaloo; Salman Daneshi; Peimaneh Sanjari; Narges Khanjani; Kiavash Hushmandi; Mehdi Raei (Journal of Pediatric and Neonatal Individualized Medicine, 2022)
Background: Phenylketonuria (PKU) is a genetic autosomal recessive disorder, which, if not treated on time, can lead to mental retardation and severe developmental delay. The aim of this study was to assess the PKU neonatal screening program in Kerman County, Iran.